Rotator side chains trigger cooperative transition for shape and function memory effect in organic semiconductors - Hyunjoong Chung (Nature Portfolio, 2018)
Martensitic transition is commonly seen in steel and shape memory alloys but rarely in organic materials. Chung et al. discover martensitic transitions in organic electronics and utilize it in designing field-effect transistors, leading to shape memory effect that in return modifies charge transport properties.